"Desperately Need a Car": Analyzing crowdfunding campaigns for car purchases and repairs on Gofundme.com. (October 2020) - Klein, Nicholas J.; Tran, Minh; Riley, Sarah
Highlights: Analyzed 325 campaigns for car purchase or repair on GoFundMe.com. Car loss often precipitated by unexpected events combined with an inability to pay. Campaigners wanted cars to access work, school, chauffer children, and medical care.